INNOVATIVE TECHNOLOGY-BASED TEACHING METHODS IN ISLAMIC RELIGIOUS EDUCATION IN PADANG CITY: SHAPING THE GOLDEN GENERATION - Aldi, Muhammad (As-Sulthan Journal of Education, 2024)
This research aims to examine the innovation of technology-based teaching methods in Islamic religious education in Padang City and its impact in forming a golden generation with noble character. Padang City was chosen as the research location because it is one of the rapidly growing centers of Islamic education in Indonesia, with various institutions that have begun to utilize technology to support the learning process. The main focus of this research is to understand the effectiveness of the application of technology in teaching, especially to improve students' religious understanding and morality. The research method used is qualitative-descriptive, with data collection techniques through in-depth interviews, direct observation, and document analysis in educational institutions in Padang City. Research participants consisted of educators, students and parents involved in the technology-based learning process. Data were analyzed using a thematic approach to explore patterns of innovation and their impact on students' character building. The results show that the application of technology in teaching Islam, such as the use of interactive applications, learning videos, and digital platforms, can increase students' interest and understanding of teaching materials. In addition, this method also provides flexibility in learning, allowing students to learn according to their own pace and style. However, the research also found some challenges, such as limited access to technology in some areas and the need for training for educators to be more adaptive to the use of technology. The implication of this research is the importance of developing a technology-based curriculum that remains grounded in Islamic values to support education in the digital era. The contribution of this research is to provide insights for education stakeholders in Padang City in designing more innovative and inclusive policies, in order to produce a golden generation that is not only intellectually smart but also superior in morals.